СПЕЦИАЛЬНОНАУЧНАЯ КАРТИНА МИРА ИСТОРИЧЕСКОЙ ДИСЦИПЛИНЫ: К ПОСТАНОВКЕ ПРОБЛЕМЫ - Кравченко, И. С. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
В статье анализируется возможность применения разработанного В.С. Степиным концепта специальнонаучной картины мира к исторической дисциплине. В исторической науке, так же как в естественных дисциплинах, существуют «идеальные объекты» дисциплинарной онтологии. Однако в исторической науке дисциплинарная онтология теряет изначальный онтологический статус, превращаясь в субъективный «образ реальности» исследователя. І.С. Кравченко СПЕЦІАЛЬНОНАУКОВА КАРТИНА СВІТУ ІСТОРИЧНОЇ ДИСЦІПЛИНИ: ДО ПОСТАНОВКИ ПРОБЛЕМИ У статті аналізується можливість застосування розробленого В.С. Стьопіним концепта спеціально наукової картини світу по відношенню до історичної дисципліни. В історичній науці, як і в природознавстві, існують «ідеальні об’єкти» дисциплінарної онтології. Однак в історичній науці дисциплінарна онтологія втрачає первісний онтологічний статус, і перетворюється на суб’єктивний «образ реальності» дослідника. Ключові слова: спеціальнонаукова картина світу, дисциплінарна онтологія, ідеальні об’єкти теоретичних схем, історична реальність. I. Kravchenko THE SPETIAL SCIENTIFIC PICTURE OF THE WORLD IN THE HISTORICAL DISCIPLINE: TOVARDS THE FORMULATION OF THE PROBLEM In this paper the possibility of application of the notion of ’special scientific picture of the world in the historical discipline is discussed. The disciplinary ontology of historical science, as well as of natural sciences, has its ideal objects. But in historical science disciplinary ontology loses the ontological status and becomes a subjective historian’s «image of reality». Key words: special scientific picture of the world, disciplinary ontology, ideal objects of theoretical schemes, historical reality.